The role of vascular and lymphatic networks in bone and joint homeostasis and pathology - Huang, Jingxiong; Liao, Chengcheng; Yang, Jian; Zhang, Liang (Frontiers in Endocrinology, 2024)
The vascular and lymphatic systems are integral to maintaining skeletal homeostasis and responding to pathological conditions in bone and joint tissues. This review explores the interplay between blood vessels and lymphatic vessels in bones and joints, focusing on their roles in homeostasis, regeneration, and disease progression. Type H blood vessels, characterized by high expression of CD31 and endomucin, are crucial for coupling angiogenesis with osteogenesis, thus supporting bone homeostasis and repair. These vessels facilitate nutrient delivery and waste removal, and their dysfunction can lead to conditions such as ischemia and arthritis. Recent discoveries have highlighted the presence and significance of lymphatic vessels within bone tissue, challenging the traditional view that bones are devoid of lymphatics. Lymphatic vessels contribute to interstitial fluid regulation, immune cell trafficking, and tissue repair through lymphangiocrine signaling. The pathological alterations in these networks are closely linked to inflammatory joint diseases, emphasizing the need for further research into their co-regulatory mechanisms. This comprehensive review summarizes the current understanding of the structural and functional aspects of vascular and lymphatic networks in bone and joint tissues, their roles in homeostasis, and the implications of their dysfunction in disease. By elucidating the dynamic interactions between these systems, we